Influence of rolling scale processing parameters on morphology of reduced iron powder particles - Внуков, Александр Александрович; Головачев, Артем Николаевич; Белая, Алена Викторовна (Technology audit and production reserves, 2016)
The use of various modes of rolling scale preparation and technological regimes of its reduction to obtain iron powder is discussed, and some of the results of original research in this field are given. The main aim of this research is to obtain a reduced iron powder with the highest level of physical and technological characteristics. The use of modern diagnostic properties of materials allows scientists to collect and analyze information received from experts around the world with the help of decision support in the field of powder materials with physical and technological characteristics of the unique complex. The prerequisites for using the reduction method for the processing of rolling production waste are discussed in the article. The complex of physical and technological properties of iron-based powder materials for production of sintered products for various applications is investigated. The presented methodology for assessing the properties of materials using advanced methods of analysis allow to obtain real information about complex of performance characteristics of iron-based powder materials. The patterns of joint influence of technological process factors on the form and size of synthesized iron powder particles are defined. A feature of the development is a comprehensive accounting and mathematical presentation of influence of scale preparation parameters (grinding feed rate, temperature and time of isothermal holding at reduction) on the surface shape and the size of the reduced iron powder particles in order to detect the presence of synergy of these factors. The regularities in the future will help to develop mathematical models to quantify the degree of influence of technological factors on the structure, physicochemical and operational properties of powder materials. The research results can be applied by experts in metallurgy and mechanical engineers to develop new resource recovery technology of rolling production waste, as well as to create new kinds of sintered powder materials with improved performance characteristics.